Graded segmental thoracic epidural anesthesia for breast reconstruction in Poland syndrome − a case report - Alka Chandra; Nallapareddy Harichandana; Shikha Chahar; Ratna Chopra; Shaleen Bhardwaj (Al-Azhar Assiut Medical Journal)
Poland syndrome, characterized by agenesis or hypoplasia of the pectoralis muscle, is a rare congenital condition. Individuals with Poland syndrome are notably susceptible to malignant hyperthermia. This case report outlines a breast reconstruction surgery performed under graded segmental thoracic epidural anesthesia, considered a safe and effective approach, even though total intravenous anesthesia is often preferred.